Wyniki leczenia wysiękowej postaci zwyrodnienia plamki związanego z wiekiem iniekcjami doszklistkowymi ranibizumabu – doniesienie wstępne - Okruszko, Anna; Borucka, Anna; Ulińska, Magdalena; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Age-related macular degeneration (AMD) is the leading cause of irreversible, severe loss of vision in the developed countries. Age-related macular degeneration (AMD) is the leading cause of irreversible, severe loss of vision in the developed countries. One of the modern methods of treatment in neovascular form of AMD are repeated intravitreal injections of ranibizumab (Lucentis®). Ranibizumab is a recombinant, humanized, monoclonal antibody that neutralizes all biologically active forms of vascular endothelial growth factor A (VEGF-A). The aim of the study was to analyze the results of intravitreal ranibizumab injections in wet AMD patients. There were 57 patients enrolled in the study. 87% of them avoided any loss of visual acuity and 47.3% gained at least one line at visual acuity chart. Authors conclude that treatment with repeated intravitreal injections of ranibizumab is effective in neovascular form of AMD.